Biosynthesis of the Pyrimidine Moiety of Thiamine Independent of the PurF Enzyme (Phosphoribosylpyrophosphate Amidotransferase) in Salmonella typhimurium: Incorporation of Stable Isotope-Labeled Glycine and Formate - Enos-Berlage, Jodi L. (American Society for Microbiology, 1999)
Genetic analyses have suggested that the pyrimidine moiety of thiamine can be synthesized independently of the first enzyme of de novo purine synthesis, phosphoribosylpyrophosphate amidotransferase (PurF), in Salmonella typhimurium. To obtain biochemical evidence for and to further define this proposed synthesis, stable isotope labeling experiments were performed with two compounds, [2-(13)C]glycine and [(13)C]formate. These compounds are normally incorporated into thiamine pyrophosphate (TPP) via steps in the purine pathway subsequent to PurF. Gas chromatography-mass spectrometry analyses indicated that both of these compounds were incorporated into the pyrimidine moiety of TPP in a purF mutant. This result clearly demonstrated that the pyrimidine moiety of thiamine was being synthesized in the absence of the PurF enzyme and strongly suggested that this synthesis utilized subsequent enzymes of the purine pathway. These results were consistent with an alternative route to TPP that bypassed only the first enzyme in the purine pathway. Experiments quantitating cellular thiamine monophosphate (TMP) and TPP levels suggested that the alternative route to TPP did not function at the same capacity as the characterized pathway and determined that levels of TMP and TPP in the wild-type strain were significantly altered by the presence of purines in the medium.